Emotional intelligence as a protective factor against cutting in adolescents (UNIHumanitas, 2020)
The main objective of this research was to describe the components of emotional intelligence in a 13-year-old adolescent girl who practices cutting. It had a descriptive design, using a qualitative, cross-sectional and non-experimental approach, through a single case study. The instruments used were the Emotional Intelligence Questionnaire, the IPDE evaluation questionnaire, and the Thinking Record. The results show that she presents clinical characteristics such as narcissistic personality disorder, avoidant personality disorder, borderline personality disorder, as well as low frustration tolerance; the psychological characteristics reveal personality conflict and strongly rooted dysfunctional thoughts that reveal an adolescent who thinks she is not worth as a person, not only physically because she has a physical disability, but also emotionally and mentally. In conclusion, it is shown that there is a relationship between low levels of the components of emotional intelligence with high frustration, feelings of worthlessness, non-acceptance and poor relationship with their parents.
Keywords: emotional intelligence; cutting; adolescence; psychopathology